2015
DOI: 10.4236/fns.2015.67067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preservation on Two Different Varieties of <i>Vernonia amygdalina</i> Del. (Bitter) Leaves

Abstract: Vernonia amygdalina Del. is one of the leafy vegetables that can be used in an attempt to alleviate the problem of micronutrient malnutrition, prominent in tropical Africa. In order to ensure availability in non-growing areas or seasons, the vegetable needs to be preserved. Processing and preservation methods influence the nutrient content of vegetables. The present study was aimed at determining the effects of preservation on two different varieties of V. amygdalina (bitter) leaves (broad and small leaves). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The reverse was the levels of MDA and NO in the treated animals. This may be due to the antioxidant properties of the extracts as these plants have been previously reported to be rich phenolic compounds (Orororo et al, 2014;Anigboro et al, 2014;Tonukari et al, 2015aTonukari et al, , 2015b. The findings of this study are also consistent with the reports of Iweala et al, (2013) and Sugumar et al, (2016).…”
supporting
confidence: 83%
“…The reverse was the levels of MDA and NO in the treated animals. This may be due to the antioxidant properties of the extracts as these plants have been previously reported to be rich phenolic compounds (Orororo et al, 2014;Anigboro et al, 2014;Tonukari et al, 2015aTonukari et al, , 2015b. The findings of this study are also consistent with the reports of Iweala et al, (2013) and Sugumar et al, (2016).…”
supporting
confidence: 83%
“…Tonukari et al. () showed that V. amygdalina contains many phytochemicals, including saponins, sesquiterpenes, lactones and flavonoids, steroid glucosides. V. amygdalina may also provide antioxidant benefit and it aqueous extract has been found to have antihelmintic, antitumor, hypoglycemic and hypolipidemic activities (Mwanauta et al., ) .…”
Section: Introductionmentioning
confidence: 99%
“…The bitterness can, however, be abated by boiling or by soaking the leaves in several changes of water (Mwanauta, Mtei, & Ndakidemi, 2014). Previous studies have indicated that V. amygdalina leaves possess many properties such as hypoglycemic, hypolipidemic and antioxidant, due to their content in bioactive phytochemicals capable of disturbing the normal metabolism and helping in the management of diabetes (Adesanoye et al, 2016;Atangwho, Egbung, Ahmad, Yam, & Asmawi, 2013;Mwanauta et al, 2014;Ong, Hsu, Song, Huang, & Tan, 2011;Tonukari, Avwioroko, Ezedom, & Anigboro, 2015). Tonukari et al (2015) showed that V. amygdalina contains many phytochemicals, including saponins, sesquiterpenes, lactones and flavonoids, steroid glucosides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Cameroon, V. amygdalina is known under the name of Ndolè and is included in the composition of the national popular dish which bears the same name. The presence of polyphenols, vitamins and mineral salts make the plant useful in human diets [25,26]. V. amygdalina is very rich in phytochemicals such as saponins, sesquiterpenes, flavonoids, and steroid glycosides (vernosides), lactones [26] and several studies reported that it has anticancer and antitumor activity [27,28]; antihepatotoxic activity [29]; hypoglycemic activity [26]; antibacterial activity [30]; anti-inflammatory [31] as well as antioxidant property [32].…”
mentioning
confidence: 99%